PENGARUH LEMBAR KERJA SISWA (LKS) TERINTEGRASI ENERGI PANAS BUMI TERHADAP PENCAPAIAN KOMPETENSI FISIKA DALAM PEMBELAJARAN IDEAL PROBLEM SOLVING PADA MATERI USAHA, ENERGI, MOMENTUM, DAN IMPULS DI KELAS XI SMAN 10 PADANG - Zulhendra Zulhendra; Ahmad Fauzi; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2016)
Low achievement of student's competencies are caused by lack of motivation and lack of problem-solving abilities of students. The effort that can be done is using geothermal energy integrated Student Worksheet for IDEAL Problem Solving learning model. The integration of geothermal energy as a real problem in lives of students is expected to increase the competencies of physics and foster energy thrift attitude in students. Solve the problems in Student Worksheet using IDEAL step Problem Solving also expected to enhance student's problem-solving abilities. The purpose of research is to investigate whether there is influence and the contribution of Student Worksheet integrated geothermal energy to the achievement of student competencies and investigate whether there is any significant impact on the achievement IDEAL problem solving competence of students' knowledge. This type of research is a quasi experimental. Design of research is randomized control group only design. The population of research is all student of grade XI MIA in the first semester of the 2015/2016 academic year. The results showed there were differences in average significant in both samples to the third-class competence. With correlation obtained contributions Student Worksheet integrated geothermal energy in the amount of 36.40% in the competence of knowledge, 60.58% on the competence of attitude, and 54.78% on competency of skills. Furthermore, the average value of the control class physics learning outcomes before and after using the model IDEAL Problem Solving also shows the average difference was significant. Based on this it can be concluded that there are significant integration and contribution of geothermal energy to the achievement of competencies of physics and there are significant problems IDEAL use soving towards the attainment of knowledge of students